2003
DOI: 10.1021/jf034288y
|View full text |Cite
|
Sign up to set email alerts
|

Determination and Confirmation of 5-Hydroxyflunixin in Raw Bovine Milk Using Liquid Chromatography Tandem Mass Spectrometry

Abstract: A method was developed and validated to determine 5-hydroxyflunixin in raw bovine milk using liquid chromatography tandem mass spectrometry (LC/MS/MS). The mean recovery and percentage coefficient of variation (%CV) of 35 determinations for 5-hydroxyflunixin was 101% (5% CV). The theoretical limit of detection was 0.2 ppb with a validated lower limit of quantitation of 1 ppb and an upper limit of 150 ppb. Accuracy, precision, linearity, specificity, ruggedness, and storage stability were demonstrated. A LC/MS/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 3 publications
0
13
1
Order By: Relevance
“…Unlike GC/MS and HPLC, LC/Q-TOF/MS/MS provides enhancement in sensitivity, with LOD of 0.10 ng/ ml that is nearly 50 times more sensitive for flunixin in plasma than that by GC/MS or HPLC [24]. Other investigators [12][13][14] using LC/MS/MS have demonstrated increased sensitivity in the determination of flunixin and 5-hydroxyflunixin in milk and meat products. Although different matrices (milk versus plasma) were involved, the LOD (0.1 ng/ml) and LOQ (1.0 ng/ml) results of this study in plasma compared favorably with those in bovine milk [12], suggesting that the limiting factors in improved sensitivity are the extent of analyte recovery and instrumentation (LC/MS/MS versus GC/MS).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike GC/MS and HPLC, LC/Q-TOF/MS/MS provides enhancement in sensitivity, with LOD of 0.10 ng/ ml that is nearly 50 times more sensitive for flunixin in plasma than that by GC/MS or HPLC [24]. Other investigators [12][13][14] using LC/MS/MS have demonstrated increased sensitivity in the determination of flunixin and 5-hydroxyflunixin in milk and meat products. Although different matrices (milk versus plasma) were involved, the LOD (0.1 ng/ml) and LOQ (1.0 ng/ml) results of this study in plasma compared favorably with those in bovine milk [12], suggesting that the limiting factors in improved sensitivity are the extent of analyte recovery and instrumentation (LC/MS/MS versus GC/MS).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators [12][13][14] using LC/MS/MS have demonstrated increased sensitivity in the determination of flunixin and 5-hydroxyflunixin in milk and meat products. Although different matrices (milk versus plasma) were involved, the LOD (0.1 ng/ml) and LOQ (1.0 ng/ml) results of this study in plasma compared favorably with those in bovine milk [12], suggesting that the limiting factors in improved sensitivity are the extent of analyte recovery and instrumentation (LC/MS/MS versus GC/MS). Thus, the increased sensitivity resulting in the improved limit of detection and quantification of flunixin in plasma would help in the regulation of the use of flunixin in racehorses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the spring of 2010, CVM collected incurred residue milk samples by treating three cows with flunixin after it was verified that the cows were healthy and had not been treated for the preceding 30 days. These incurred samples were provided to the IFSH for testing (1). Daily a.m. and p.m. milkings were collected until the prescribed drug clearance withhold time (4 days) and frozen.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, 5-hydroxyflunixin has been established as the marker residue to be used for monitoring of flunixin residues in bovine milk (5). More recently, an LC-tandem MS (LC-MS/MS) method was developed for the determi nation and confirmation of 5-hydroxyflunixin at 1-and 2ppb levels, respectively, in unpasteurized bovine milk (1).…”
mentioning
confidence: 99%